The Rulings on the Successive Hands of the Usurper - Abu sulieh, Balqees Talal; Aljarrah, Jihad Mohammad (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: This study aims to clarify the concept of successive hands as used in Islamic jurisprudence, explain the rulings related to the successive hands stemming from the usurper’s possession, identify the legal responsibility of each of these hands, and establish the legal foundation for such responsibility in light of both Jordanian civil law and Islamic jurisprudence. Methods: A descriptive and analytical approach was adopted by presenting the relevant provisions of the Jordanian Civil Code concerning usurpation and analyzing their conformity with the principles and rulings of Islamic jurisprudence. Results: The Jordanian legislator does not differentiate between the various hands that succeed the usurper’s possession of property. All such hands are treated equally as hands of guarantee, regardless of whether the possession occurred in good faith and based on a lawful transaction, or in bad faith through usurpation or by taking possession from the original usurper. Conclusion: The Jordanian legislator should take into consideration the principle of good faith in property-related transactions and distinguish between possession acquired through good faith and lawful transactions, and possession resulting from bad faith or usurpation. It is necessary to reconsider the prevailing rule that "every hand resulting from the usurper’s possession is a hand of guarantee" and instead recognize the legal disparity between different types of possession.